2019
DOI: 10.3390/ma13010026
|View full text |Cite
|
Sign up to set email alerts
|

A Compressive Peak Strength Model for CFRP-Confined Thermal Insulation Materials under Elevated Temperature

Abstract: In this paper, a compressive peak strength model for CFRP-confined thermal insulation materials under elevated temperature was proposed. The thermal insulation material was made by Portland cement with different portions of perlite. The compressive strengths of four different perlite ratios in weight, such as 0%, 10%, 20%, and 30% of thermal insulation materials, confined by one-layer, two-layer, and three-layer carbon fiber-reinforced polymer (CFRP) composite materials, were obtained. The test results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For the maximum compressive strength of the thermal-insulating material at elevated temperatures, an exponential thermal softening model was proposed as follows [ 38 , 39 ]: where f’ T and f’ c are the maximum compressive strengths of the thermal-insulating material under an elevated temperature ( T ) and the reference temperature ( T ref ), respectively. In Equation (9), λ is the thermal softening parameter of the thermal-insulating materials with various perlite ratios added.…”
Section: Constitutive Model Of the Thermal-insulating Materials At mentioning
confidence: 99%
“…For the maximum compressive strength of the thermal-insulating material at elevated temperatures, an exponential thermal softening model was proposed as follows [ 38 , 39 ]: where f’ T and f’ c are the maximum compressive strengths of the thermal-insulating material under an elevated temperature ( T ) and the reference temperature ( T ref ), respectively. In Equation (9), λ is the thermal softening parameter of the thermal-insulating materials with various perlite ratios added.…”
Section: Constitutive Model Of the Thermal-insulating Materials At mentioning
confidence: 99%
“…Razvi and Saatcioglu (1998) proposed a constraint equation for high-strength concrete [29]. Li's research proposed the constitutive models for normal-strength and low-strength cylindrical concrete confined with CFRP, which was adopted from the Mohr-Coulomb failure theory to predict the compressive strength of CFRP-confined concrete [30][31][32][33][34]. Wang et al (2012) found that the CFRP-confined-squarecross-section column failed suddenly via CFRP rupture at the corner of the column, and a modified confinement pressure model was proposed which considered the influence of cross-section size, effective rupture strain of CFRP, as well as hoop reinforcement [35].…”
Section: Introductionmentioning
confidence: 99%